Genera of the leaf-feeding Dendrothripinae of the world (Thysanoptera, Thripidae), with new species from Australia and Sulawesi, Indonesia - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2016)
Character states used in distinguishing taxa within the Thripidae subfamily Dendrothripinae are discussed, and a key presented to the 11 genera recognized worldwide. Comments on each of these genera are provided, together with keys to the species from Australia of Dendrothrips, Ensiferothrips and Pseudodendrothrips. From Australia are described, four new species of Dendrothrips, one of Pseudodendrothrips, and a remarkable new species of Ensiferothrips that has required a re-diagnosis of that genus. Another new species of Ensiferothrips is described from Sulawesi, thus greatly extending the known geographical range of this previously Australian genus.